Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Day 1 Tue, August 11, 2015 2015
DOI: 10.2118/174666-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-Surfactant-Polymer (ASP) Flooding of Crude Oil at Under-Optimum Salinity Conditions

Abstract: ASP flooding achieves high incremental oil recovery factors over water flooding by reducing the interfacial tension (IFT) to ultralow values and by ensuring good mobility control, provided by the polymer. Traditionally, this has been achieved by tuning the ASP flood so that it is at optimum salinity conditions, i.e. Winsor type III micro-emulsion phase. Systematic studies of the performance of ASP at different (non-optimum) salinities are scarce, while operating at lower salinities condition can offer several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Thus, the equilibrium IFT between the injected surfactant fluid and crude oil as present in a phase behavior experiment could be a representation of the phases in contact within a particular porous medium, but this may not be true for all systems . Recent studies have shown that high oil recovery is also possible under nonoptimum salinity conditions. ,, This was also the case in the series of experiments conducted in which the highest oil recovery was observed under Type II– or sub-optimum salinity conditions in the work by Battistutta et al Thus, new studies often contradict the conventional early studies. Hence, there is no clear ASP flooding strategy defining the region of salinity that is favorable for an efficient process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the equilibrium IFT between the injected surfactant fluid and crude oil as present in a phase behavior experiment could be a representation of the phases in contact within a particular porous medium, but this may not be true for all systems . Recent studies have shown that high oil recovery is also possible under nonoptimum salinity conditions. ,, This was also the case in the series of experiments conducted in which the highest oil recovery was observed under Type II– or sub-optimum salinity conditions in the work by Battistutta et al Thus, new studies often contradict the conventional early studies. Hence, there is no clear ASP flooding strategy defining the region of salinity that is favorable for an efficient process.…”
Section: Introductionmentioning
confidence: 99%
“…All input parameters ( a 31 , a 32 , and b 3 ) need to be specified at a reference permeability ( k ref ). Since we did not measure the amount of surfactant that remained in the core during surfactant flooding in the performed FACF core-floods, we used the average surfactant adsorption in the Bentheimer sandstones measured earlier for the same type of surfactant slug: 0.25 ± 0.12 mg/g rock. Note that this value for surfactant retention lies within the ranges measured by others who performed surfactant retention measurements for a large number of cores .…”
Section: Resultsmentioning
confidence: 99%
“…The latter yields a drastic increase in capillary number. The extent to which a constant surfactant concentration, at a fixed pH, can lower the o/w IFT of a specific oil–water–surfactant system is essentially controlled by the salinity of the water phase. ,, At under-optimum salinity conditions, an oil-in-water microemulsion (ME) coexists with excess oil (type II– system). However, at over-optimum salinity, a water-in-oil microemulsion is in equilibrium with excess water (type II+ system).…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge of the low-salinity environment is the inability to set varying salinities based on ASP components; the high value is better for preflush, the low salinity could be positive on a polymer drive by maintaining a consistent polymer viscosity, while salinity close to the optimum salinity helps mobilize residual oil through ASP slug. The salinity gradient, i.e., the modification of salinities from the preflush, ASP mixture, and polymer in sequence, has been studied in an effective way to produce more residual oil [2,[8][9][10][11][12][13]. Difficulty in maintaining designed salinities at specific locations and conditions inhibits the positive effects of the salinity gradient, e.g., the mixture of formation brine, and ASP slug can change salinities during fluid transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…Gregersen et al [10] analyzed the impacts of anhydrite on ASP performance under low-salinity conditions. Battistutta et al [11] analyzed ASP flooding under optimum salinity conditions, i.e., 2.5-4.5 wt % NaCl, and showed the alteration of ASP slug would be negligible at this high salinity. Chen et al [12] performed ASP coreflooding experiments using different III-I, I-III-I, II-III-I, and III-III-III salinity profiles and concluded that negative salinity was favorable.…”
Section: Introductionmentioning
confidence: 99%